1985
DOI: 10.1111/j.1432-1033.1985.tb09223.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of intestinal microvillar proteins. Evidence for an intracellular sorting taking place in, or shortly after, exit from the Golgi complex

Abstract: Pig small intestinal mucosal explants, labelled with [35S]-methionine, were fractionated into Mg2+-precipitated (intracellular and basolaterdl) and microvillar membranes, and the orientation of newly synthesized aminopeptidase N (EC 3.4.1 1.2) in vesicles from the two fractions was studied by its accessibility to proteolytic cleavage. The mature polypeptide of M , 166000 from the latter fraction was cleaved by trypsin, proteinase K and papain, consistent with an extracellular location of the enzyme at its site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…1). Similar results have been obtained in studies of protein targeting in the small intestine (32), although conflicting reports using a similar model, in the small intestine, have been reported by two different laboratories (33,34). Clearly, a basolateral to apical membrane "tract" exists as hepatocytes, enterocytes, and transfected MDCK cells use this transport pathway for the transcytosis of polymeric Igs (35).…”
supporting
confidence: 75%
“…1). Similar results have been obtained in studies of protein targeting in the small intestine (32), although conflicting reports using a similar model, in the small intestine, have been reported by two different laboratories (33,34). Clearly, a basolateral to apical membrane "tract" exists as hepatocytes, enterocytes, and transfected MDCK cells use this transport pathway for the transcytosis of polymeric Igs (35).…”
supporting
confidence: 75%
“…While all of these results are extremely interesting, cell fractionation studies are always open to the criticism that difficult-to-control-for and difficult-to-measure cross-contamination may artifactually skew the results. Similar experiments in other laboratories suggest that microvillar proteins are vectorially sorted in intestinal cells (Danielsen and Cowell, 1985).…”
Section: A Sorting Pathwayssupporting
confidence: 80%
“…Based on this approach, some authors concluded that the apical glycoproteins in the basolateral membrane fraction were transiently integrated before the apical markers reached the BB domain (Hauri et al, 1979;Quaroni et al, 1979). Others postulated that an intracellular sorting of plasma membrane glycoproteins was involved and that the apical markers used took a direct pathway from the Golgi apparatus to the BB domain (Ahnen et al, 1982;Danielsen and Cowell, 1985). The discrepancies between the results of all these studies have always been blamed on the subcellular fractionation procedures used, the purity of the membrane fractions, and the possible cross-contamination of the basolateral membrane fraction by the intracellular membrane fraction (e.g., Golgi apparatus, intracellular vesicles).…”
Section: Biogenesis Of the Two Plasma Membrane Domains Of Enterocytesmentioning
confidence: 96%